Enhancing postgraduate students' learning outcomes through Flipped Mobile-Based Microlearning - Abdulrahman M. Al-Zahrani (Association for Learning Technology, 2024)
This study examines the effects of implementing a Flipped Mobile-Based Microlearning (FMM) approach on postgraduate students' accessibility, engagement, knowledge retention, overall learning experience and academic achievement. A quantitative multiple methods approach was employed, utilising a two-group quasi-experimental design and a survey questionnaire to gather data. The results suggest that the FMM approach may have positive effects on accessibility, engagement, knowledge retention, overall learning experience and final exam scores when compared to the traditional learning approach. The findings support the efficacy of integrating FMM, highlighting its potential for enhancing the learning process and academic outcomes. These results have implications for educational practice and research, emphasising the value of technology-enhanced learning approaches, active and interactive learning experiences and the promotion of student motivation and attitudes towards learning. This study underscores the broader applicability of FMM and suggests its potential for improving educational outcomes across different educational levels and subject areas.